Medicações intracanal contra o biofilme de Enterococcus faecalis e sua influência na resistência de união do material obturador e microdureza da dentina - Dalla Lana, Daniel de Lima (2019)
The aim of this study was to evaluate the antimicrobial action of different intracanal medications against Enterococcus faecalisbiofilm and its effect on the bond strength of the obturator material and dentin microhardness. A hundread and twenty six human extracted roots were prepared and and sterilized. Samples were randomly divided into 6 groups: saline, chlorhexidine gel 2%, calcium hydroxide, grape seed extract, calcium hydroxide + chlorhexidine gel 2% and grape seed extract + chlorhexidine gel 2%. For the microbiological stage, the roots inoculated for 15 days with Enterococcus faecaliswere used (n=10). A percentage of microbial reduction was calculated based on counts of colony forming units before and after treatments. Bond strength tests were performed at two times, 21 days and 12 months after obturation, by push out test (n=15). Microhardness test used the average of 3 indentations for the comparisons (n=10). Fifteen days of contact was the standardized treatment period for the medications. Data were tabulated and statistically analyzed at a significance level of 2 Intracanal medications against Enterococcus faecalisbiofilm and its effect on the bond strenght of the obturator material and dentin microhardness 5%. Medications containing calcium hydroxide and grape seed extract, both with chlorhexidine vehicle, demonstrated the highest values of bacterial reduction (p <0.05). Grape seed extract medications resulted in the highest bond strength values of obturator material to the root canal dentin at the two time intervals tested (p <0.05). Medications based on calcium hydroxide or grape seed extract did not modify the microhardness of the dentin tissue (p> 0.05).